2013
DOI: 10.3109/0886022x.2013.828356
|View full text |Cite
|
Sign up to set email alerts
|

Rescue therapy with sirolimus in a renal transplant recipient with tacrolimus-induced hepatotoxicity

Abstract: Calcineurin inhibitors at elevated serum concentrations frequently cause mild elevation of the liver chemistries. Although rare, severe hepatotoxicity is their serious complication. A 54-year-old man with end-stage renal disease due to chronic glomerulonephritis without biopsy received a renal allograft from the deceased donor. Eleven days after transplantation severe liver injury (AST up to 421 IU/L, ALT 1242  IU/L, and GGT 212 IU/L) with the serum bilirubin within the normal range was recorded. Tacrolimus tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…For example, one study reported that tacrolimus eventually resulted in cholestatic jaundice 60 days post-liver transplantation with increases in both alkaline phosphatase (ALP) and total bilirubin (TBIL) levels ( Taniai et al, 2008 ). Another study showed that liver enzyme levels increased significantly 12 days post-renal transplantation, with aspartate aminotransferase (AST) elevated to 421 U/L, alanine aminotransferase (ALT) at 1242 U/L, and serum TBIL levels within the normal range ( Mesar et al, 2013 ). Today, increasing accessibility to digital health data owing to the transition to electronic health records, together with the rising costs and known limitations of traditional clinical trials, real-world data offer enhanced research efficacy, which bridges the evidentiary gap between clinical research and practice ( Corrigan-Curay et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study reported that tacrolimus eventually resulted in cholestatic jaundice 60 days post-liver transplantation with increases in both alkaline phosphatase (ALP) and total bilirubin (TBIL) levels ( Taniai et al, 2008 ). Another study showed that liver enzyme levels increased significantly 12 days post-renal transplantation, with aspartate aminotransferase (AST) elevated to 421 U/L, alanine aminotransferase (ALT) at 1242 U/L, and serum TBIL levels within the normal range ( Mesar et al, 2013 ). Today, increasing accessibility to digital health data owing to the transition to electronic health records, together with the rising costs and known limitations of traditional clinical trials, real-world data offer enhanced research efficacy, which bridges the evidentiary gap between clinical research and practice ( Corrigan-Curay et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Franco-Esteve et al reported only a single incidence of hepatotoxicity among 47 patients treated with mTOR inhibitor monotherapy and Jacques et al reported severe sirolimus-inducedacutehepatitis 19,20. Interestingly sirolimus was a rescue therapy in one KTR who experienced tacrolimus-related hepatotoxicity 15. We found only one case of sirolimus related hepatotoxicity.…”
Section: Discussionmentioning
confidence: 47%
“…Taniai et al presented a case in which hepatotoxicity was induced by both tacrolimus and cyclosporine after living donor liver transplantation 14. A case presented by Mesar et al reported complete resolution of LFTA after withdrawal of calcineurin inhibitor (tacrolimus) and replacement with sirolimus 15. It is important to be aware of the possible association of tacrolimus with hepatotoxicity in order to discontinue therapy and replace with sirolimus in cases of hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…An early increase in liver enzyme levels in kidney transplant patients may be a clinical manifestation of cytomegalovirus cytomegalovirus (CMV) infection, as well as the effect of one or more immunosuppressive therapy or the presence of a primary hepatocellular abnormality involving the bile duct. 20 In the patient group of this study, an increase was observed in AST and ALT values in the first week after transplantation. Transient elevated liver enzyme levels are a common finding in kidney transplant recipients, usually within a month of transplant.…”
Section: Discussionmentioning
confidence: 55%